INVESTIGATION OF HEMP (CANNABIS SATIVA L.) FIBRE QUANTITY AND QUALITY AS INFLUENCED BY GENOTYPE AND SEED RATE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The investigation on hemp fibre quantity and quality as influenced by genotype and seed rate was carried out at the Upytė Experimental Station Lithuanian of the Lithuanian Research Centre for Agriculture and Forestry in 2014. Bi-factorial trial was carried out: Factor A – variety (A1 – USO 31; A2 – Bialobrzeskie); Factor B – sowing rate (B1 – 45 kg ha-1; B2 – 70 kg ha-1). Data showed that variety (genotype) had a significant influence on fibre content (after dew-retting as well after water-retting) – it was higher for variety Bialobrzeskie and amounted to 37.2 and 34.5%, respectively. Seed rate (or crop density) did not show significant influence neither on fibre content nor on fibre quality (flexibility, strength) parameters.